1979
DOI: 10.1111/j.2517-6161.1979.tb01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Bandit Processes and Dynamic Allocation Indices

Abstract: The paper aims to give a unified account of the central concepts in recent work on bandit processes and dynamic allocation indices; to show how these reduce some previously intractable problems to the problem of calculating such indices; and to describe how these calculations may be carried out. Applications to stochastic scheduling, sequential clinical trials and a class of search problems are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
749
2
6

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,113 publications
(758 citation statements)
references
References 17 publications
1
749
2
6
Order By: Relevance
“…Our presentation of bandit problems is quite sketchy, and we send the reader to specialized references such as (Gittins 1979(Gittins , 1989Whittle 1982;Berry and Fristedt 1985).…”
Section: Comparison Of Rewards and Strategies In A One-armed Bandit Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Our presentation of bandit problems is quite sketchy, and we send the reader to specialized references such as (Gittins 1979(Gittins , 1989Whittle 1982;Berry and Fristedt 1985).…”
Section: Comparison Of Rewards and Strategies In A One-armed Bandit Pmentioning
confidence: 99%
“…This durable good problem differs from the non durable good problem (discussed previously), since in the former case information acquisition has a constant cost, while in the latter it has an endogenous cost given that examination means consumption. The solution of this search model, with repetitive consumption has been worked out in clinical trials and in economics; it is known as the armed bandit problem (see Gittins 1979Gittins , 1989Berry and Fristedt 1985).…”
mentioning
confidence: 99%
“…A relaxed version of the restless bandit problem is introduced, and the problem can be solved optimally in polynomial time. Based on this relaxed version, a priority-index heuristic policy is proposed to reduce to the optimal Gittins index policy [30] in the special case of the multi-armed bandit problem. However, the Whittle's index heuristic can be only applied when the restless bandit problem satisfies a certain indexability property, which is hard to check [21,31].…”
Section: Solving the Restless Bandit Problemmentioning
confidence: 99%
“…He introduces a priority policy that relies on an index which can be computed for each job based on the properties of a job, but not on other jobs. Gittins [12] showed that this priority index is a special case of his Gittins index [12,13]. Twenty years after Sevcik presented the priority policy, Weiss [33] formulated Sevcik's priority index again in terms of the Gittins index and provided a different proof of the optimality of the priority policy.…”
Section: Preemptionmentioning
confidence: 99%